Análisis del cambio de cobertura vegetal en el Páramo Bordoncillo – franja del municipio de Santiago Putumayo, años 2017 y 2022, a través del uso de herramientas de sistemas de información geográfica (SIG) (2023)
The moors are a very fragile vegetation cover, a reservoir of wild flora and fauna and have an extensive system of streams that conduct large amounts of water, hence the importance of their maintenance, protection and conservation. Human intervention and climate change have impacted the Páramo Bordoncillo, specifically in the fringes of the municipality of Santiago Putumayo, where activities such as the construction of road infrastructure and coal extraction have caused negative consequences for this ecosystem.